European infrastructures for sustainable agriculture. (October 2017) - Roy, Jacques; Tardieu, François; Tixier-Boichard, Michèle; Schurr, Ulrich
The European infrastructures EMPHASIS and AnaEE aim to collaborate in bringing innovative solutions for a sustainable intensification of agriculture. By integrating the study of plant phenomics and agricultural ecology they hope to foster the development of novel scientific concepts, sensors and integrated models.